Can the corneal tissue be used as a wound dressing material for skin injuries?. (January 2021) - Bulut, N.
Abstract: Currently, the application field of corneal tissue is corneal transplantation from animal to human or from human to human. Although the cornea and skin emerge from the same embriyological layer, ectoderm, and the cornea has a very high capacity, no research has been conducted to reveal the effect of the cornea in skin wound healing. There is no commercial product available in the hospital pharmacy that contains a ready-to-use, hygienic, wound dressing material manufactured from cornea for both ocular or extraocular wounds. In this article, the feasibility of corneal tissue as a candidate for disposable wound dressing material for skin injuries are examined and compared with the closest alternative, amnion membrane.